Determining Antigen Specificity of Human Islet Infiltrating T Cells in Type 1 Diabetes - Nakayama, Maki; Michels, Aaron W. (Frontiers in Immunology, 2019)
Type 1 diabetes, the immune mediated form of diabetes, represents a prototypical organ specific autoimmune disease in that insulin producing pancreatic islets are specifically targeted by T cells. The disease is now predictable in humans with the measurement of type 1 diabetes associated autoantibodies (islet autoantibodies) in the peripheral blood which are directed against insulin and beta cell proteins. With an increasing incidence of disease, especially in young children, large well-controlled clinical prevention trials using antigen specific immunotherapy have been completed but with limited clinical benefit. To improve outcomes, it is critical to understand the antigen and T cell receptor repertoires of those cells that infiltrate the target organ, pancreatic islets, in human type 1 diabetes. With international networks to identify organ donors with type 1 diabetes, improved immunosequencing platforms, and the ability to reconstitute T cell receptors of interest into immortalized cell lines allows antigen discovery efforts for rare tissue specific T cells. Here we review the disease pathogenesis of type 1 diabetes with a focus on human islet infiltrating T cell antigen discovery efforts, which provides necessary knowledge to define biomarkers of disease activity and improve antigen specific immunotherapy approaches for disease prevention.